Learning-Based Human Segmentation and Velocity Estimation Using Automatic Labeled LiDAR Sequence for Training - Wonjik Kim; Masayuki Tanaka; Masatoshi Okutomi; Yoko Sasaki (IEEE Access, 2020)
In this paper, we propose an automatic labeled sequential data generation pipeline for human segmentation and velocity estimation with point clouds. Considering the impact of deep neural networks, state-of-the-art network architectures have been proposed for human recognition using point clouds captured by Light Detection and Ranging (LiDAR). However, almost all conventional datasets are either a collection of single LiDAR scanning with label information or sequential LiDAR scanning without label information. This limitation has disturbed the progress of research to date. Therefore, we have developed an automatic labeled sequential data generation pipeline, in which we can control any parameter or data generation environment with pixel-wise and per-frame ground truth segmentation and pixel-wise velocity information for human recognition. Our approach uses a precise human model and reproduces a precise motion to generate realistic artificial data. We present more than 7K sequences, where each sequence consists of 32 frames generated by the proposed pipeline. With the proposed sequence generator, we confirm that human segmentation performance is improved when using the sequential data compared to when using the data from a single LiDAR scan. We also evaluate our data by comparing with data generated under different conditions. In addition, we estimate pedestrian velocity with LiDAR by only utilizing data generated by the proposed pipeline.